1994
DOI: 10.1021/bp00027a015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Dioxide, Air Flow Rate, and Inoculation Density on the Batch Growth of Catharanthus roseus Cell Suspensions in Stirred Fermentors

Abstract: A high reproducibility of batch growth of Catharanthus roseus could only be achieved by using identical inoculum material. It was found that the initial growth rate of the cells increased with increasing inoculation density, whereas the maximum growth rate was not affected. Withdrawal of the conditioned medium from the inoculum resulted in a strong decline in the initial growth rate, indicating that conditioning factors affected the initial growth rate. Neither increasing the air flow rate from 0.5 to 1.5 volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…The same result was obtained in hairy root culture of T. paniculatum that showed the increasing of initial inoculum density can cause increasing of saponin content (Manuhara et al, 2012). According to Van Gulik et al (1994), the high of initial inoculum density can eliminated lag phase of growth curve, so specific growth rate became maximum. The high of growth rate indicated that the culture have long of exponential phase.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The same result was obtained in hairy root culture of T. paniculatum that showed the increasing of initial inoculum density can cause increasing of saponin content (Manuhara et al, 2012). According to Van Gulik et al (1994), the high of initial inoculum density can eliminated lag phase of growth curve, so specific growth rate became maximum. The high of growth rate indicated that the culture have long of exponential phase.…”
Section: Discussionsupporting
confidence: 60%
“…But, if the initial inoculum density is high, the lag phase in cell culture does not occur because of the direct growth to be in the exponential phase. This suggests that increased secondary metabolites along with increased number of cells (Van Gulik et al, 1994;Sakurai et al, 1996). So, this experiment was conducted to optimization of the culture conditions of T. paniculatum Gaertn.…”
Section: Introductionmentioning
confidence: 99%
“…For example, culturing sycamore cell suspensions in conditioned medium reduced the minimum effective density for growth from 9-15 × 10 3 cell/mL to 1.0-1.25 × 10 3 cell/mL (Stuart and Street, 1971). In suspension cultures of C. roseus, conditioned medium significantly enhanced the rate of dry-weight accumulation in aerated bioreactors (van Gulik et al, 1994). However, none of these studies have evaluated the effects of conditioned medium on the formation of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Large explants generally survive more frequently and grow more rapidly than relatively small explants at the initial stage of culture [24]. Inoculation density was found to affect the activities of individual enzymes in suspended plant cell cultures for the synthesis of secondary metabolites [25]. The higher final cell mass could be achieved in the cell culture with higher inoculum sizes.…”
Section: Discussionmentioning
confidence: 98%